Recovery of Critical Metals from E-Waste Printed Circuit Boards (PCBs) Via Acid Leaching - Akor, Joel E.; Balogun, Ayo F. (Journal of Sustainable Materials Processing and Management, 2024)
In this research, the study focused on recovering critical metals from E-waste Printed Circuit Boards (PCBs) using a hydrometallurgical approach that involves leaching in a chloride-based solution. The investigation examined how various leaching parameters, such as acid concentration, reaction temperature, particle size, and leaching duration, influenced the efficiency of dissolving critical metals. A kinetic model was developed to represent how these variables affected the leaching rate. The raw HP waste computer desktops (HP WPCBs) primarily consisted of Propylene, (C3H6) n 54-1936; Sasaite, 031-0020; Silicon oxide, SiO2 82-1558and Impure copper oxide CuO 10-1329. The results obtained from the Energy-Dispersive X-ray Fluorescence (EDXRF) analysis supported the findings of X-ray Diffraction (XRD). Under the optimized leaching conditions, 81.8% of the critical metals dissolved within 120 minutes, and the leaching process was predominantly controlled by a surface layer mechanism. The estimated activation energy (Ea) of 55.79 kJ/mol further supported this dissolution mechanism.